COVID-19 impact on kidneys - Orczykowski, Maciej; Oleszczuk, Rafał; Grzebalska, Agnieszka (Journal of Education, Health and Sport, 2022)
Introduction and purpose The COVID-19 pandemic, which has been ongoing since early 2020, has significantly affected the health care system worldwide. SARS-CoV-2 virus being the etiological factor of the disease has a high affinity for the renal organ. The purpose of this study was to provide an overview of the current knowledge of the problem of frequent AKI in the course of coronavirus infection, the impact of COVID-19 disease in patients with chronic kidney disease and on renal replacement therapy or dialysis. Review method In the process of writing, we used available articles and scientific papers in Pubmed and Google Scholar databases based on keywords: COVID-19, SARS-CoV-2, AcuteKidneyInjury, ChronicKidneyDisease. State of knowledge SARS-CoV-2 virus enters target cells through the ACE2 receptor. In the pathophysiology of AKI in the course of COVID-19, a key role is attributed to secondary damage mechanisms such as cytokine storm, hypoperfusion with hypoxia, endothelial dysfunction. The incidence of acute kidney injury ranges from 5.1% to 36.6%. The development of AKI, renal transplant status, the presence of chronic kidney disease or renal replacement therapy is associated with an increased risk of severe course and higher mortality on COVID-19. Summary The COVID-19 pandemic has posed new logistical and therapeutic challenges to the health care system. Due to the high tropism of SARS-CoV-2 to the kidneys and the frequent occurrence of AKI during the course of the infection, nephrology patients, those on renal replacement therapy and those awaiting transplantation should be placed under special surveillance. Patients in these groups are at particular risk for a severe course of COVID-19.